Effect of three polychaetes on growth and reproductive performance, biochemical indices and histology of different tissues in the female Pacific white shrimp, Litopenaeus vannamei broodstock - Shuaipeng Li; Hao Liu; Weibin Huang; Shipei Yang; Mingsheng Xie; Menglong Zhou; Baiquan Lu; Biao Li; Beiping Tan; Yuanzhi Yang; Xiaohui Dong (Animal Nutrition, 2025)
A 30-day feeding trial was conducted to assess the effect of three fresh-live polychaetes as diets on growth and reproductive performance, biochemical indices and histology of different tissues in female Pacific white shrimp (Litopenaeus vannamei) broodstock. Two novel polychaete species, Marphysa maxidenticulata (MM group) and Perinereis nuntia (PN group), and a traditional species, Perinereis aibuhitensis (PA group), were used as a single diet and individual experimental groups, respectively. A total of 225 healthy female broodstock shrimp, initial weight of 59.70 ± 0.18 g, were randomly divided into three groups (three replicates of 25 shrimp each). The results showed that the MM group outperformed the PA and PN groups in growth indices, with the highest weight gain, specific growth rate, molting rate, protein efficiency ratio, gonadosomatic index, and lower feed conversion ratio compared to the PN group (P < 0.05). Regarding reproductive performance, the MM group had the highest daily number of sexually mature female broodstock shrimp, successful mating count, maturity rate, mating rate, spawning cycle, total number of fertilized eggs, individual fertilized egg yield, area of mature oocytes, total number of nauplii, naupliar yield/shrimp, hatching rate, and the lowest naupliar deformity rate than the other two groups (P < 0.05). Moreover, compared to the PA and PN groups, the MM group demonstrated superior activities of lipid metabolism-related enzymes and digestive enzymes, and antioxidant capacity in the hepatopancreas, intestine and serum, as well as reduced malondialdehyde levels. Meanwhile, the ovaries of the MM group showed a significant accumulation of triglycerides, estradiol, and vitellogenin compared to the other groups. Histology revealed more developed secretory cells in the hepatopancreas and larger mature oocytes in the MM group compared to the others. In conclusion, M. maxidenticulata can maximize growth, reproductive performance, the activities of lipid metabolism-related enzymes and digestive enzymes, antioxidant and immune ability of female broodstock shrimp. This study demonstrated that M. maxidenticulata could be used as a potential fresh-live diet for the female L. vannamei broodstock.